2018
DOI: 10.1002/nafm.10229
|View full text |Cite
|
Sign up to set email alerts
|

Sheepshead Foraging Patterns at Oil and Gas Platforms in the Northern Gulf of Mexico

Abstract: In the northern Gulf of Mexico, there are over 2,000 oil and gas platforms (hereafter, "platforms") that are de facto artificial reefs. The ecological importance of platforms is the subject of debate, but little information exists on the extent to which fish feed on platform-dwelling benthic organisms. We used a camera array to characterize the frequency and duration of incidents in which Sheepshead Archosargus probatocephalus foraged on platformdwelling benthic organisms. We also characterized abundances and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Indeed, a concurrent study found that Sheepshead frequently forage on platform‐dwelling organisms (Reeves et al. ). It is notable that Sheepshead muscle isotopic values were highly variable and were not tightly clustered around barnacles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, a concurrent study found that Sheepshead frequently forage on platform‐dwelling organisms (Reeves et al. ). It is notable that Sheepshead muscle isotopic values were highly variable and were not tightly clustered around barnacles.…”
Section: Discussionmentioning
confidence: 99%
“…Sheepshead were collected at platforms adjacent to those where stone crabs, barnacles, algae, and sediment were collected to avoid biasing concurrent studies of Sheepshead abundances and grazing behaviors (Reeves et al. , ). Sheepshead were collected using hook and line and spears; stone crabs, barnacles, and macroalgae were collected from the platform's main pilings.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations